Travel for survive! Identifying the antecedents of vaccine tourists' travel intention: Using a stimulus-organism-response model - Wang, Xue-Bing; Chen, Chien-Chao; Ku, Gordon Chih Ming; Chen, Che-Hsiu; Hsu, Chin Hsien; Lee, Peng-Yeh (Frontiers in Public Health, 2022)
The COVID-19 global pandemic and the uneven distribution of vaccines have resulted in alternative medical tourism, vaccine tourism. The purpose of this study is to identify the antecedents of vaccine tourists’ travel intention. The Stimulus-organism-response model was used as a framework to understand the relationship between risk perception (stimulus), pandemic prevention attitude (organism), decision making (organism), and travel intention (response) in vaccine tourism. An online questionnaire survey method was adopted to address the purpose of the research. Purposive and snowball sampling were used to select eligible respondents who were over 18 years old and had experience in vaccine tourism. A total of five hundred and twenty online questionnaires were collected, and description analysis, confirmatory factor analysis, and structural equation modeling were utilized to analyze the collected data. The findings indicated that pandemic prevention attitude is a full mediator between risk perception and travel intention. There is a significant causal relationship between risk perception and pandemic prevention attitude and between pandemic prevention attitude and travel intention. Furthermore, tourists’ travel decision-making also significantly influences their travel intention. However, the relationship between tourists’ risk perception and travel decision-making has no significant effect. Vaccine tourism was created based on the COVID-19 context. Therefore, in order to avoid vaccine travel becoming an infection control breach, pandemic prevention planning and the medical quality of the destination, and the prevention policies between the countries should be completely assessed and conducted.